Neurological Manifestations in Familial Mediterranean Fever: Results of 22 Children from a Reference Center in Kayseri, an Urban Area in Central Anatolia, Turkey - Canpolat, Mehmet; Gumus, Hakan; Gunduz, Zubeyde; Dusunsel, Ruhan; Kumandas, Sefer; Bayram, Ayşe Kaçar; Yel, Sibel; Poyrazoglu, Hatice Gamze; Yilmaz, Kenan; Doganay, Selim; Yikilmaz, Ali; Dundar, Munis; Per, Huseyin (Neuropediatrics, 2017)
Background Familial Mediterranean fever (FMF) is an inherited inflammatory disorder characterized by attacks of fever with polyserositis.Objective The purpose of this study was to evaluate pediatric patients with FMF who had central nervous system (CNS) findings.Materials and Methods Our medical records database for 2003 to 2014 was screened retrospectively. In total, 104 patients with FMF were identified, 22 of whom had undergone neurological examination for CNS symptoms.Results Neurological findings included headache in 16 patients (72.7%), epilepsy in 6 patients (27.3%), pseudotumor cerebri in 2 patients (9.1%), multiple sclerosis in 1 patient (4.5%), and tremor in 1 patient (4.5%). The most common MEFV gene mutation was homozygous M694V (40.9%).Conclusions Patients with FMF can present with various CNS manifestations. Further studies that include large populations are needed to elucidate the neurological manifestations of FMF.
Keywords: familial Mediterranean fever; neurological manifestations; M694V mutation; children